KAJIAN KUAT TARIK BELAH PADA PERENCANAAN BETON DENGAN ADDITIVE SILICA FUME MENGGUNAKAN METODA AMERICAN CONCRETE INSTITUTE (AGREGAT HALUS GUNUNG SUGIH DAN AGREGAT KASAR TANJUNGAN LAMPUNG) - Sari Utama Dewi (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2016)
During the tensile strength of concrete is very difficult to measure than concrete press. Your analysis and experimental research on the use of additives such as Silica Fume and Sikament-NN was conducted to determine the value of the concrete tensile strength variation Silica Fume adding 0%, 5%, 10%, 15% and 20%. This study used a sample test cylinder diameter of 15 cm and height of 30 cm were perfomed at age 28 days and required 3 test specimens for each of the various levels of the addition of Silica Fume and Sikament-NN. With the addition of Silica Fume 4 variation of 5%, 10%, 15% and 20% and Sikament-NN 0.5%, 1%, 1.5% and 2% of the test specimen obtained a total of 27 units of the test specimen. The result showed that the influence of Silica Fume on the concrete mix can increase kelecakan concrete, it is influenced by particle shape Silica Fume smooth particles. The greater the importance of the use of Silica Fume slump value is small, it is because of Silica Fume absorbs water. On the use of Silica Fume 15% at 28 days of concrete age obtained optimum tensile strength of concrete is 41.52 kg/cm2, but the result have not yet reached the planned tensile strength that is equal to 60 kg/cm2. Use of Silica Fume as additive in concrete with cement replacement levels of > 15% of the weight of cement can reduce the quality of concrete. It is due to water absorption by Silica Fume too large so that the water needed for the hydration is not enough lead into a low concrete strenght. From table-NN Sikament addition of 0.5% and Silica Fume 15% at 28 days of concrete to increase the strength of the highest (551.07 kg/cm2) compared to the percentage that the addition of another 1%, 1.5% and 2% for the addition Sikament-NN and 5%, 10% and 20% for the addition of Silica Fume, from research and from the statements above show that the compressive strength of concrete with the addition of Sikament-NN of 0.5% and Silica Fume for 15% was recommended for use on a concrete plan when using additional materials as mentioned above. Means it can be concluded the use Sikament-NN and Silica Fume should be used to the extent of 0.5% and 15% and more of it is not effective anymore.